2015
DOI: 10.1007/s40534-015-0070-6
|View full text |Cite
|
Sign up to set email alerts
|

Measurement methods and analysis tools for rail irregularities: a case study for urban tram track

Abstract: Rail irregularities, in particular for urban railway infrastructures, are one of the main causes for the generation of noise and vibrations. In addition, repetitive loading may also lead to decay of the structural elements of the rolling stock. This further causes an increase in maintenance costs and reduction of service life. Monitoring these defects on a periodic basis enables the network rail managers to apply proactive measures to limit further damage. This paper discusses the measurement methods for rail … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 22 publications
0
18
0
Order By: Relevance
“…For trains to run on time the condition of the infrastructure must be sufficient [3]. The purpose of a railway track is to provide a stable, safe, and efficiently guided platform for the train to run at various speeds with different axle loadings [24]. There are two types of railway tracks: conventional ballasted tracks and slab tracks [5].…”
Section: Railway Infrastructurementioning
confidence: 99%
See 1 more Smart Citation
“…For trains to run on time the condition of the infrastructure must be sufficient [3]. The purpose of a railway track is to provide a stable, safe, and efficiently guided platform for the train to run at various speeds with different axle loadings [24]. There are two types of railway tracks: conventional ballasted tracks and slab tracks [5].…”
Section: Railway Infrastructurementioning
confidence: 99%
“…Sleepers transfer the load from the vehicles into the ballast and are constructed of concrete. The ballast bed anchors the track, creates bearing capacity for the track, and prevents lateral and longitudinal movement [27]. The sub-ballast is the prime track foundation; it prevents vertical movements based on the thickness of the subgrade [26].…”
Section: Railway Infrastructurementioning
confidence: 99%
“…The conclusions in [24] show that proactive solutions are needed to reach the desired goals of improved safety, improved availability, and improved reliability. Chiacchiari and Loprencipe in [25] concluded that rail irregularities, particularly those in urban railway infrastructures, are one of the main causes of noise and vibration generation. Monitoring defects on a periodic basis enables a network's rail managers to apply proactive measures to limit further damage.…”
Section: Introductionmentioning
confidence: 99%
“…It has proven effective to combine numerical studies together with experimental results in studies on the subway induced vibration. Chiacchiari [39] discussed measurement methods for rail corrugation and proposed an application method for rail irregularities. Kaynia [40] performed a measurement of the vibration induced railway embankment by high speed trains and developed a rigorous numerical model for the prediction of ground response.…”
Section: Introductionmentioning
confidence: 99%